2008
DOI: 10.1111/j.1600-6143.2007.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Insulin Response to Arginine in Deceased Donors Predicts the Outcome of Human Islet Isolation

Abstract: Despite a stringent donor selection, human islet isolation remains frustratingly unpredictable. In this study, we measured acute insulin response to arginine (AIRarg), an in vivo surrogate measure of islet mass, in 29 human deceased donors before organ donation, and correlated values with the outcome of islet isolation. Thirteen isolations (45%) met the threshold for clinical islet transplantation. Among all measured donor characteristics, the only discriminating variable between successful or unsuccessful iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Islets were isolated from ABO-compatible deceased donor pancreata with a negative cross-match and evaluated as previously described (8). The access to the portal vein was gained under general anesthesia by percutaneous catheterization of a peripheral portal branch under ultrasound guidance or by surgical catheterization of a small mesenteric vein.…”
Section: Methodsmentioning
confidence: 99%
“…Islets were isolated from ABO-compatible deceased donor pancreata with a negative cross-match and evaluated as previously described (8). The access to the portal vein was gained under general anesthesia by percutaneous catheterization of a peripheral portal branch under ultrasound guidance or by surgical catheterization of a small mesenteric vein.…”
Section: Methodsmentioning
confidence: 99%
“…Exploring this hypothesis in large mammalian models, we indeed confirmed that the main determinant of islet isolation outcome is the donor islet mass itself. In two studies, in the pig [5] and in humans [6], the pancreatic endocrine mass was assessed by determination of the acute insulin response (AIR) [7] in the donor. Stimulation by injection of arginine is preferred in human organ donors because it does not affect glycaemia and does not interfere with the functioning of other organs, whereas glucose can be used as an alternative in experimental studies, as employed in our pig model [5].…”
Section: Air Acute Insulin Responsementioning
confidence: 99%
“…Floyd et al first identified that intravenous arginine administration increases the insulin concentration in the blood circulation (16). Thus, the intravenous arginine load test is clinically used as the non-glucose promoting secretion test to evaluate the function of islet β-cells in patients with T2DM (17-20), leading to the exploration of the oral arginine load test.…”
Section: Discussionmentioning
confidence: 99%